2013
DOI: 10.1016/j.laa.2013.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Hermitian matrices with a bounded number of eigenvalues

Abstract: Conjugation covariants of matrices are applied to study the real algebraic variety consisting of complex Hermitian matrices with a bounded number of distinct eigenvalues. A minimal generating system of the vanishing ideal of degenerate three by three Hermitian matrices is given, and the structure of the corresponding coordinate ring as a module over the special unitary group is determined. The method applies also for degenerate real symmetric three by three matrices. For arbitrary n partial information on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Matrices with repeated eigenvalues have been studied in contexts from geometry [3] to classical invariant theory and linear algebra [6,7,8,14,16,18,19,20]. Recently, they have come to focus in the study of curvature of algebraic varieties [4].…”
Section: Jnf Of a Type A Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrices with repeated eigenvalues have been studied in contexts from geometry [3] to classical invariant theory and linear algebra [6,7,8,14,16,18,19,20]. Recently, they have come to focus in the study of curvature of algebraic varieties [4].…”
Section: Jnf Of a Type A Matrixmentioning
confidence: 99%
“…In a refinement of the study of degenerate matrices, some authors [7,8,19] have studied matrices by their number of distinct eigenvalues. In this situation, the role of the matrix discriminant is played by the set of k-subdiscriminants.…”
Section: Jnf Of a Type A Matrixmentioning
confidence: 99%
“…So the stable multiplicity (see [6] for more about this) of L C (χ t ) in the degree d-piece of k[N ] is the number of partitions of d of length t. For the weight χ t changing the order of the arguments in (8) gives the same element up to a sign. So (8) gives us a candidate spanning set labelled by partitions of length t (lower all indices by 1) and by the above the elements of this set labelled by partitions of degree d and length t would have to be independent for big n. 5. Computer calculations show that the answer to the question from [24, §4] (Remark 3 above) is in general no.…”
Section: Denote the Variety Of N×m-matrices By Matmentioning
confidence: 99%
“…Computer calculations show that the answer to the question from [24, §4] (Remark 3 above) is in general no. For example, for n = 4 and χ = (2, 1, −1, −2) the elements from (8) give only a 1-dimensional space of invariants in degree 6 and not the required 2 dimensions. However, it turns out that in all cases were I found that the elements from (8) don't span, replacing E λ by a suitable Sym t × Sym t -conjugate does give a spanning set.…”
Section: Denote the Variety Of N×m-matrices By Matmentioning
confidence: 99%